Iron deficiency anaemia: pathophysiology, assessment, practical management. Issue 1 (7th January 2022) - Kumar, Aditi; Sharma, Esha; Marley, Alexandra; Samaan, Mark A; Brookes, Matthew James
Abstract : The WHO has recognised iron deficiency anaemia (IDA) as the most common nutritional deficiency in the world, with 30% of the population being affected with this condition. Although the most common causes of IDA are gastrointestinal bleeding and menstruation in women, decreased dietary iron and decreased iron absorption are also culpable causes. Patients with IDA should be treated with the aim of replenishing iron stores and returning the haemoglobin to a normal level. This has shown to improve quality of life, morbidity, prognosis in chronic disease and outcomes in pregnancy. Iron deficiency occurs in many chronic inflammatory conditions, including congestive cardiac failure, chronic kidney disease and inflammatory bowel disease. This article will provide an updated overview on diagnosis and management of IDA in patients with chronic conditions, preoperative and in pregnancy. We will discuss the benefits and limitations of oral versus intravenous iron replacement in each cohort, with an overview on cost analysis between the different iron formulations currently on the market.